2022
DOI: 10.1155/2022/5419671
|View full text |Cite
|
Sign up to set email alerts
|

A CFD Study on the Design Optimization of Airborne Infection Isolation Room

Abstract: Airborne infection isolation (AII) rooms are used to accommodate patients with highly infectious diseases and keep the released pathogens to limit the risk of cross-infection. This paper proposes a concept for an AII room made from two shipping containers to handle the scarcity of hospital beds when the COVID-19 disease spreads over the world. The proposed system consists of the main isolation room, anteroom, and toilet as well as other functional areas. In addition, the main isolation room was modeled with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the ventilation performance of the negative-pressure isolation room was also verified depending on the operation of the exhaust fan in the attached toilet [6], and the extent of air pollution spread was investigated according to the negative-pressure control in the outpatient area of the hospital [7]. Previous studies have proposed design methods for AIIR ventilation systems and highlighted key considerations for both the design [8] and the operation [9] of HVAC systems. However, the scope of previous studies is limited to isolated patient rooms in conventional buildings, and few studies have evaluated airflow analysis and ventilation performance in modular buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ventilation performance of the negative-pressure isolation room was also verified depending on the operation of the exhaust fan in the attached toilet [6], and the extent of air pollution spread was investigated according to the negative-pressure control in the outpatient area of the hospital [7]. Previous studies have proposed design methods for AIIR ventilation systems and highlighted key considerations for both the design [8] and the operation [9] of HVAC systems. However, the scope of previous studies is limited to isolated patient rooms in conventional buildings, and few studies have evaluated airflow analysis and ventilation performance in modular buildings.…”
Section: Introductionmentioning
confidence: 99%
“…led to an increase in the velocity of the airflow in the room. Le, Nguyen and Kieu [13] suggested that changing the location of the exhaust air grilles could improve the ventilation performance in an airborne isolation room. Research also showed that human movement or sliding door motion could adversely impact the air velocity, pressure field and contaminant distribution, within general ventilated or specific negative pressure isolation rooms [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) is known as an important technology for the study of the hydro-aerodynamic characteristics of fluid motion, and has been applied to a microchannel, sterilization chamber, torpedo-shaped underwater glider, centrifugal blower, an infection isolation room, etc. [7][8][9][10][11][12][13][14]. Le et al [7][8][9][10] investigated the thermocapillary migration of the fluid flows in a microchannel.…”
Section: Introductionmentioning
confidence: 99%